Elevating sustainability: the role of machining in modern eco-friendly manufacturing processes - Baizura Zubir,; Jaharah A. Ghani,; Saima Yaaqob,; Nizaroyani Saibani,; Afifah Zakiyyah Juri,; Che Hassan Che Haron,; Nurul Sakinah Abdul Basir,; Nurul Fatini Ismail,; Natasha Ereena Mohd Nasir,; Nur Izati Abustarim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sustainable manufacturing has become a critical concern across various industries, including aerospace, automotive, and services. It involves the creation of manufactured products through economically sound processes that minimize negative environmental impacts while conserving energy and natural resources. Additionally, sustainable manufacturing aims to enhance employee, community, and product safety.This paper focuses on the machining process as a key component of sustainable manufacturing. Machining is widely used in manufacturing industries to fabricate components, but it also significantly contributes to environmental pollution. Sustainable machining has been a topic of discussion for over a decade. In sustainable machining processes, every factor acts differently like, the tool life, productivity, and effective utilization of resources must be increased. In contrast, the machining cost, machine cutting power, and adverse effect of cooling and lubrication fluids will be decreased. Important aspects of sustainable machining include dry and near-dry machining, cryogenic machining, and minimum quantity lubricant (MQL) were presented in this article. The effectiveness of these processes is assessed based on cutting tool life and the quality of machined components. In addition, the advancements consideration such as novel process variations, process hybridization, the use of sustainable tools and green transfer mediums, and the optimization of process parameters. Recommendations include increasing efficiency and reducing waste by incorporating recyclable tools in the machine industry implementing either stand alone or hybrid sustainable lubrication machining techniques.